PEMETAAN WILAYAH SEBARAN COVID-19 UNTUK PEMBENTUKAN DESA TANGGUH BENCANA DI DESA SIMO, KECAMATAN SIMO, KABUPATEN BOYOLALI - Fitriyah; Aida Nur Azqiya; Dicky Ardiyanto; Dwiki Alvian; Evrina Rakhmanita; Fadhila Firda Azzahra; Hanan Sri Widyantoro; Istiyanti Nur Marfu’ah; Putry Rusmawati; Riska Nur Azizah (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2022)
Condition of the spread corona virus disease 2019 (Covid-19) in 2020 to 2021 experienced quite a number of cases in Indonesia, the implementations of Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) and various preventions were carried out by the the goverments to suppres the spread of Covid-19. Simo Village, Boyolali Regency is the first village to experience Covid-19 casses in Boyolali Regency with a fairly high rate a Covid-19 spread form June 2020 to February 2021. Simo Village is one of the villages located not far form Simo Market accebilities with a high level of interaction people between residents who are accompanied by a number of employes (PNS) form outside the area who often go out have caused a massive spread of the Covid-19 virus to occur. Covid-19 data (recap data) in Simo Village provide clues in the form of active, recovered, and death. With this data processing, a mapping of the distributions of active cases in several hamlets or villages can be made so that it can provide an overview to the residents concerned for an inrotmative and efficient map. With this mapping, it can be analyzed, the level of vulnerability, potential disaster, and risk suppression